HUBUNGAN PANJANG TULANG FEMUR DENGAN TINGGI BADAN PADA SUKU BATAK DI KELURAHAN SUDIREJO I KECAMATAN MEDAN KOTA - AGUNG PRATAMA SIREGAR; IRFAN DARFIKA LUBIS (JURNAL ILMIAH SIMANTEK, 2022)
Identification is an important examination to determine the identity of a person in forensic anthropology. Body length is one of the parameters to help determine a person’s biological profile. Measurement of body length and femur length has a good correlation. This research method is a descriptive analytic method with cross-sectional design approach. The subject of research were 32 bataknese living in Sudirejo I Medan village, consisting of men and women who met the inclusion and exclusion criteria. The sampling technique uses purposive sampling. Femur length and body length was positively and significantly with coefficient correlation ranging from 0,715 to 0,916 (p=0,000). The linier regression formula shows the Standard Error of The Estimate (SEE) ranging from 1,787 to 5,243 (p=0,000). there is a significant correlation between femur length and body length. So, the body length can be estimated by measuring femur length with linear regression equation.